Optimization-based search for nordsieck methods of high order with quadratic stability polynomials - Cardone, Angelamaria; Jackiewicz, Zdzislaw; Mittelmann, Hans (Mathematical Modelling and Analysis, 2012)
We describe the search for explicit general linear methods in Nordsieck form for which the stability function has only two nonzero roots. This search is based on state-of-the-art optimization software. Examples of methods found in this way are given for order p = 5, p = 6, and p = 7.